Pengaruh Model Problem Based Learning Berbantuan Software Geogebra terhadap Kemampuan Pemecahan Masalah Matematika - Nida Aisyah (Universitas Indraprasta PGRI, 2016)
The aim of the experiment research is to know the effect of the Problem Based Learning Model helped by software geogebra on mathematics problem solving. This research was conducted in Junior High School As-Syafiih 02 on academic year 2015/2016, true experimental designed was used in this research in the form of posttest only control design. Sample was taken randomly, it was in VII-A as an experiment group and VII-B as a control group. Data was taken from each group by posttest that consists of 7 items in essay that includes four aspects of assessment to solve the problem. The insrument has been tested and all the items were valid and got the highest level of reliability. Data analysis in this research was done by descriptive and inferential by ttest, normality test and homogenity test too. The result shows that there is the significant effect of problem based learning model helped software geogebra on mathematics problem solving, especially in two dimention shape.